2016
DOI: 10.1016/j.rppede.2015.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Fine particulate matter estimated by mathematical model and hospitalizations for pneumonia and asthma in children

Abstract: Objective:To estimate the association between exposure to fine particulate matter with an aerodynamic diameter <2.5 microns (PM2.5) and hospitalizations for pneumonia and asthma in children.Methods:An ecological study of time series was performed, with daily indicators of hospitalization for pneumonia and asthma in children up to 10 years of age, living in Taubaté (SP) and estimated concentrations of PM2.5, between August 2011 and July 2012. A generalized additive model of Poisson regression was used to estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 26 publications
1
21
0
6
Order By: Relevance
“…Likewise, a study in Taubaté, SP, which has a population similar to that of Volta Redonda, also found an association between exposure to PM 2.5 , at concentrations similar to those of Volta Redonda, and hospitalizations due to pneumonia and asthma among children. 13 Chronic and sub-chronic exposure to fine particulate matter, among other pollutants, was shown to be a risk factor for hospitalization due to acute bronchiolitis among children in California. 19 Using logistic regression, those authors showed that there was an association between exposure to PM 2.5 and the outcome of hospitalization due to acute bronchiolitis; and that an increase in PM 2.5 concentration of 10 µg/m 3 increased the odds of hospitalization by 9% (95% CI: 1.04-1.14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, a study in Taubaté, SP, which has a population similar to that of Volta Redonda, also found an association between exposure to PM 2.5 , at concentrations similar to those of Volta Redonda, and hospitalizations due to pneumonia and asthma among children. 13 Chronic and sub-chronic exposure to fine particulate matter, among other pollutants, was shown to be a risk factor for hospitalization due to acute bronchiolitis among children in California. 19 Using logistic regression, those authors showed that there was an association between exposure to PM 2.5 and the outcome of hospitalization due to acute bronchiolitis; and that an increase in PM 2.5 concentration of 10 µg/m 3 increased the odds of hospitalization by 9% (95% CI: 1.04-1.14).…”
Section: Discussionmentioning
confidence: 99%
“…5,[12][13][14] The importance of studying how exposure to this pollutant can act on human health comes from the fact that, because of its aerodynamic diameter (less than 2.5 microns), it can remain suspended in the air for a longer time and thus be transported over longer distances and also reach deeper portions of the respiratory system.…”
Section: Introductionmentioning
confidence: 99%
“…This model is used operationally by the Center for Weather Forecasting and Climate Studies of the Brazilian National Institute for Space Research (CPTEC/INPE) in an operational base. It estimates PM 2.5 concentrations every three hours, resulting in eight estimates made by the model at 40m aboveground, with a resolution of 25x25km 13,14 ; Recent applications of data estimated by CCATT-BRAMS in epidemiological studies can be found in César et al 15,16 , Silva et al 17 , Nascimento et al 18 , and Carmo et al 19 .…”
Section: Introductionmentioning
confidence: 99%
“…César et al 22 estimaram a associação entre exposição ao material particulado fino com as internações por pneumonia e asma em crianças com até 10 anos, em Taubaté e usaram o modelo aditivo generalizado de regressão de Poisson para estimar o risco relativo, com defasagem de zero até cinco dias após a exposição; o modelo unipoluente foi ajustado pela temperatura aparente, medida definida a partir da temperatura e umidade relativa do ar, sazonalidade e dia da semana. Os valores dos riscos relativos para internações por pneumonia e asma foram significativos para lag 0 (RR=1,051; IC95% 1,016-1,088); lag 2 (RR=1,066; IC95% 1,023-1,113); lag 3 (RR=1,053; IC95% 1,015-1,092); lag 4 (RR=1,043; IC95% 1,004-1,088) e no lag 5 (RR=1,061; IC95% 1,018-1,106).…”
Section: Tabela 5 -Média Móvel E Riscos Relativos Para O Ozônio Na Inunclassified